2014
DOI: 10.21236/ada621151
|View full text |Cite
|
Sign up to set email alerts
|

Designing Incentives for Marine Corps Cyber Workforce Retention

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instruction, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to ABSTRACT (maximum 200 words)There is a pervasive national shortage of qualifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Self-concept refers to the self-constructed beliefs that one holds about oneself and the responses of others (Oyserman, Elmore & Smith, 2012 The predominant factor from this theme was, however, motivation. This is in line with international literature that says understanding what motivates people and how to effectively motivate them are key components in any successful career (Hernandez & Johnson, 2014). Motivation can be divided into two components, intrinsic motivation, which has to do with the psychological compensation that an individual receives from the work, and extrinsic motivation, which relates to the economic rewards of the job.…”
Section: Self-conceptsupporting
confidence: 80%
See 3 more Smart Citations
“…Self-concept refers to the self-constructed beliefs that one holds about oneself and the responses of others (Oyserman, Elmore & Smith, 2012 The predominant factor from this theme was, however, motivation. This is in line with international literature that says understanding what motivates people and how to effectively motivate them are key components in any successful career (Hernandez & Johnson, 2014). Motivation can be divided into two components, intrinsic motivation, which has to do with the psychological compensation that an individual receives from the work, and extrinsic motivation, which relates to the economic rewards of the job.…”
Section: Self-conceptsupporting
confidence: 80%
“…The findings point to the importance of attributes associated with candidates' positive self-concept of which intrinsic motivation was found to be a powerful factor. This was related to various meaningful objectives like money, ambition and status (Hernandez & Johnson, 2014). Findings from this research study suggested that drivers of intrinsic motivation for these individuals were personal but also universal in their power to motivate.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…It is also worth noting that many of the concerns about hiring and retention of cyber personnel that our participants discussed in this study are not localized to USAF. For example, similar concerns about cyber workforce recruiting and retention issues have been explored in the U.S. Army (e.g., U.S. Government Accountability Office [GAO], 2019a; Wenger, O'Connell, and Lytell, 2017), the U.S. Marine Corps (e.g., Hernandez and Johnson, 2014), and the U.S. Navy (Bayer et al, 2019). In addition, a 2019 GAO report (GAO, 2019b) cited hiring and retaining key cybersecurity management personnel as a major concern among all 23 of the U.S. federal agencies that GAO included in its study.…”
Section: Some Final Notes On the Ongoing And Shared Challenges Of Rec...mentioning
confidence: 99%